Embryonic and larval development of Lipophrys pholis (Pisces: Blenniidae) - Faria, Cláudia Barreiros Macedo de (2012)
Information on the early ontogeny of Lipophrys pholis is scattered and incomplete. In this paper we describe for the first time the full developmental sequence from egg to juvenile in controlled conditions. In addition, some notes on the spawning behaviour of adults and the behaviour of larvae are provided. During oviposition, the female follows the male´s path, suggesting that the male may apply sperm on the nest before spawning. Embryonic development lasted 16 days (17ºC) and larval development to settlement lasted 29 days (15.5-17.5ºC). At hatching, mean larval total length was 5.0 mm. The larvae hatched with the mouth and anus opened, with pigmented eyes and almost no yolk, and started to feed within one day. They first settled 29 days after hatching (13-14 mm TL) and showed full juvenile pigmentation and behaviour 8 to 9 days later (17-19 mm TL).